Lessons learned from implementing injury and illness surveillance in professional football: introducing a new implementation framework - Tabben, M.; Hassanmirzaei, B.; Singh, G.; Miladi, R.; Chaabane, M.; McCourt, P.; Serner, A.; Clarsen, B.; Ellouze, Z.; Mokrani, M.; Whiteley, R.; D`Hooghe, P.; et al. (Sports Medicine, 2025)
Injury and illness surveillance (IIS) systems play a crucial role in professional sports by monitoring athlete health, informing preventive strategies, and enhancing performance. Although international bodies, such as the International Olympic Committee, have established comprehensive guidelines, implementing these standards across diverse sports environments and specifically in football (soccer), remains challenging. This paper reflects on the experiences gained from implementing IIS systems in various football settings, including the Qatar Stars League and the Asian Football Confederation. It explores the successes and challenges encountered while adapting surveillance protocols to specific contexts and introduces a framework aimed at standardizing and optimizing IIS implementation. The findings underscore the importance of centralized oversight, routine data collection, and stable staffing to ensure consistent data quality. The integration of electronic data tools and real-time monitoring has further improved data accuracy and reporting. However, maintaining engagement across large geographical regions and addressing regulatory variations continue to pose challenges. We propose a step-by-step framework for IIS implementation that addresses these complexities while providing a strong foundation for expanding surveillance across other sports settings. This framework seeks to promote a more consistent approach to injury prevention and health management, with the potential for universal validation through collaboration with experts worldwide.